CPT1A Supports Castration-Resistant Prostate Cancer in Androgen-Deprived Conditions - Molishree Joshi; Gergana E. Stoykova; Maren Salzmann-Sullivan; Monika Dzieciatkowska; Lauren N. Liebman; Gagan Deep; Isabel R. Schlaepfer (Cells, 2019)
Prostate cancer (PCa) is the most common cancer in men, and the global burden of the disease is rising. The majority of PCa deaths are due to metastasis that are highly resistant to current hormonal treatments; this state is called castration-resistant prostate cancer (CRPC). In this study, we focused on the role of the lipid catabolism enzyme CPT1A in supporting CRPC growth in an androgen-dependent manner. We found that androgen withdrawal promoted the growth of CPT1A over-expressing (OE) tumors while it decreased the growth of CPT1A under-expressing (KD) tumors, increasing their sensitivity to enzalutamide. Mechanistically, we found that CPT1A-OE cells burned more lipid and showed increased histone acetylation changes that were partially reversed with a p300 specific inhibitor. Conversely, CPT1A-KD cells showed less histone acetylation when grown in androgen-deprived conditions. Our results suggest that CPT1A supports CRPC by supplying acetyl groups for histone acetylation, promoting growth and antiandrogen resistance.